PROFIL USAHA RUMAH JAMUR GEMAH RIPAH DESA BUMIREJO KECAMATAN KALIANGRIK KABUPATEN MAGELANG - JAWA TENGAH Profile of Gemah Ripah Mushroom Farm In Bumirejo Village, Kaliangkrik District, Magelang Regent, Province of Central Java - Sasongko, Lutfi Aris (Universitas Wahid Hasyim, 2005)
The research explored oyster mushroom cultivation which was done by Gemah Ripah Mushroom Farm as middle-size agricultural business enterprise that located at Bumirejo Village, Kaliangkrik District, Magelang Regent, Province of Central Java. The primary data was taken from case study of the cultivation, the secondary data was taken from Central Statistic Bureau and other related research. From the research could conclude : 1) technical aspect, cultivated area had appropriated with oyster mushroom habitat; 2) social aspect, Gemah Ripah Mushroom Farm could create employment for local community; 3) commercial aspect, oyster mushroom demand as one of high protein alternative vegetable was still increase; 4) financial aspect, counting with assume age of project was five years, getting income on the second month of first year, rate of interest was 16 % each year and reside value was zero. Investment amount of Rp. 27,149,500 would give net B/C 1.462 with NPV Rp. 101,211,980.51 and IRR 143.797 %. That investment would achieve payback period on 23rd month. Operational cost each year Rp. 59,746,838.88 and cost each item Rp. 447.84. Average income each month Rp. 8,620,000 and average product each month 1,580 kgs. SWOT analyze included : (1) Strength : the investment was enough for business development, entrepreneur skill on management was enough, production equipment was having appropriated design and function, production capacity was big enough, customer was loyal, Gemah Ripah led on white oyster mushroom market in M agelang; (2) Weakness : Gemah Ripah had not had own land yet (they still rent from land-owner), the management did not open new market actively, their research and development skill on white oyster mushroom cultivation still narrow; (3) Opportunity : the big opportunity to build new market (refer to increased demand each year, especially many distributor which agree to take trading contract), changing of consumer trend that consume more high protein vegetables; (4) Threat : increasing the amount of competitor which destroyed price market, increasing the price of fuel.Key words : oyster cultivation, SWOT analyze